Short Communication: Morphology and taxonomic relationships of shallot (Allium cepa L. group aggregatum) cultivars from Indonesia - Nita Fitriana; Ratna Susandarini (Society for Indonesian Biodiversity, 2019)
Abstract. Fitriana N, Susandarini R. 2019. Short Communication: Morphology and taxonomic relationships of shallot (Allium cepa L. group aggregatum) cultivars from Indonesia. Biodiversitas 20: 2809-2814. Shallot is an important vegetable crop commodity in Indonesia, and its ranks third in terms of cultivation area after chili (Capsicum annuum L.) and cabbage (Brassica oleracea L.). There are a number of superior cultivars of this species that have been studied in terms of their morpho-agronomic traits, but their morphological variability and its implication to taxonomic relationships have not been studied in depth. This study aimed at documenting morphological variability and taxonomic relationships of 12 superior shallot cultivars using numerical taxonomic approaches. Sixteen morphological characters from leaves and bulbs were used in cluster analysis and principal component analysis. The results revealed that twelve shallot cultivars from Indonesia showed significant variability in leaf and bulb morphology, particularly in quantitative characteristics as indicated from ANOVA. The grouping of cultivars and their taxonomic relationships generated from cluster analysis and principal component analysis revealed the role of bulb morphology as determining characteristics in the grouping of cultivars. This study suggested the importance of bulb morphology in the characterization of shallot cultivars.